Evaluación financiera de la industria del cemento, cal y yeso en Colombia (2014-2019) (2021)
The research reported in this article aims to evaluate the financial performance of the cement, lime and gypsum industry in Colombia in the 2014-2019 period. The static and trend analysis of accounting and value management indicators that measure its growth, efficiency, efficacy, effectiveness, economic value added (EVA) and market value added (VMA) was used as a methodology. It is found that this sector increases its sales and assets but reduces its net profit; it is effective in obtaining profits, following the changing direction of efficacy in controlling expenditures, which is amplified by positive financial leverage. However, it destroys EVA in the last four years, due to the deterioration of the after-tax return on net operating assets, which was exceeded by the cost of capital. These findings can be complemented with studies for homogeneous groups in age, size and legal nature.